Cinema como recurso tecnológico para o ensino de competências socioemocionais - Costa, Darlea Araújo de Souza Esteu da (2017)
The purpose of this study was to investigate the feasibility of using cinema as a technological resource to promote the development of socio-emotional competences and contribute to the educational itinerary of the high school students of the Federal Institute of Education Science and Technology of Amazonas (IFAM), Campus Manaus - Industrial District (CMDI). The rationale of this study discussed the role of cinema in education and the importance of enabling the student to develop their emotional at school. For the development of the study we used the Research-action as a research methodology and for data collection we used the Focus Group techniques and the Conversation Wheel. For the study of social-emotional competences in this research, we present the relevance of the education of emotions in school and are based on the theory of the so-called Big Five, also known as Five Factors Model (MCF), Global Factors of Personality or Five Great Factors, model of organization of personality traits that explain groups of behaviors: Conscientiousness, Agreeableness, Neuroticism (Emotional Stability), Openness to experiences and Extraversion. For the identification of the competence to be promoted, a questionnaire was applied and from this result we elaborated criteria for the choice of the film and consequently the planning of the didactic session for the data collection. The results obtained attest to the relevance of this study and allowed to prove the efficacy of the cinema in the promotion of socio-emotional competences besides presenting new perspectives for the inclusion of social-emotional education in the school. In order to consolidate our study and promote social-emotional education in school through the cinema, we developed a didactic guide for teachers entitled "Didactic Guide for the Promotion of Social-emotional Competences with Cinema", which aims to encourage and instigate the teaching of social-emotional skills in schools through the cinema.